Mobility and sales activity during the Corona crisis: Daily indicators for Switzerland - Florian Eckert; Heiner Mikosch (ETH Zurich, KOF Swiss Economic Institute, 2020)
This paper documents daily compound indicators on physical mobility and sales activity in Switzerland during the Corona crisis. We report several insights from these indicators: The Swiss population substantially reduced its activities already before the shops closed and before the authorities introduced containment policies in mid-March 2020. Activity started to gradually recover from the beginning of April onwards, again substantially before the first phase of the shutdown easing started at the end of April. Low physical mobility during the second half of March and during April likely contributed to the quick fall in new COVID-19 infections since mid-March. The sharp drop in economic activity in consumer-related services during March and April and the gradual recovery in these sectors since May correlates strongly with the reduction and subsequent gradual resurgence of mobility. In addition, while activity within Switzerland was back to normal levels by late June, activity of Swiss residents outside of Switzerland was still below normal.
hdl:20.500.11850/437812
Keywords: C38; D12; E32; H12; I12; 330; Corona crisis; mobility; sales activity; daily indicators